Systemic inflammatory response due to chloroform intoxication: an uncommon complication - Dettling, Andrea; Stadler, K.; Eisenbach, Christoph; Skopp, Gisela; Haffner, Hans-Thomas (International journal of legal medicine, 2016)
Well-known adverse effects of chloroform are drowsiness, nausea, and liver damage. Two cases with an uncommon complication due to chloroform intoxication are presented. In the first case, a general physician, because of nausea and dyspnea, admitted a 34-year-old woman to hospital. She developed a toxic pulmonary edema requiring mechanical ventilation for a few days, and a systemic inflammatory response syndrome (SIRS) with elevated white blood cell counts, a moderate increase of C-reactive protein, and slightly elevated procalcitonin levels. There were inflammatory altered skin areas progressing to necrosis later on. However, bacteria could be detected neither in blood culture nor in urine. Traces of chloroform were determined from a blood sample, which was taken 8 h after admission. Later, the husband confessed to the police having injected her chloroform and put a kerchief soaked with chloroform over her nose and mouth. In the second case, a 50-year-old man ingested chloroform in a suicidal attempt. He was found unconscious in his house and referred to a hospital. In the following days, he developed SIRS without growth of bacteria in multiple blood cultures. He died several days after admission due to multi-organ failure. SIRS in response to chloroform is a rare but severe complication clinically mimicking bacterial-induced sepsis. The mechanisms leading to systemic inflammation after chloroform intoxication are currently unclear. Possibly, chloroform and/or its derivates may interact with pattern recognition receptors and activate the same pro-inflammatory mediators (cytokines, interleukins, prostaglandins, leukotrienes) that cause SIRS in bacterial sepsis.